Distribution Truck Route Optimisation at UDMB Using The Clarke and Wright Savings and Cluster First Route Second - Maulidina, Fayza; Sitania, Farida Djumiati; Wahyuda, Wahyuda (Faculty of Engineering, Andi Djemma University, 2025)
UDMB is a distributor company of frozen food products in East Kalimantan and North Kalimantan. Time and distance are the biggest obstacles felt by companies in the distribution process. It is because the product must be at a minimum temperature of -18o Celsius so that the product remains in good condition. Meanwhile, the cooling machine on a distribution truck can only maximize working temperature for 6 hours. These travel time and distance problems have occurred more than 12 times a year in out-of-town distribution. Therefore, this research aims to produce an optimal distribution routes with consideration of the fastest time and shortest distance. This problem is solved using the Clarke and Wright Savings Method with the Head and Tail concept and the Cluster First Route Second Method with Sweep Algorithm and Nearest Neighbor. Then, the total distribution time and distance between the results of the two methods are compared. Based on the first results, the total trucks used are 3 units with a total distribution time of 847 minutes and a total distribution distance of 475.8 km. Based on the second results, the total trucks used are 3 units with a total distribution time of 875 minutes and a total distribution distance of 483.8 km. This shows that the Clarke and Wright Savings Method with the Head and Tail concept is the method that produces the most optimal route with the fastest total distribution time and shortest total distribution distance.